Pengaruh Kualitas Pelayanan, Sarana Prasarana dan Promosi dalam Meningkatkan Minat Baca di Perpustakaan Al-Hikam - Moh Ulil Ampri; Eka Farida; Restu Millaningtyas (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract The purpose of this study was to determine the effect of service quality, infrastructure and promotion on increasing reading interest. The research used is a quantitative method. The population in this study were the students of the Al-Hikam Malang Islamic boarding school as many as 356 students. While the samples used in this study were 78 samples. The data used is primary data using a questionnaire. The data analysis method used is instrument test: validity and reliability test, normality test, classic assumption test: multicollinearity test and heteroscedasticity test, multiple linear regression analysis, hypothesis testing: simultaneous test, partial test and coefficient of determination. From the results of the study simultaneously obtained results that service quality, infrastructure and promotion have a significant effect on reading interest, service quality variable has a positive effect on reading interest, infrastructure variable has no significant positive effect on reading interest and promotion variable has no significant positive effect on reading interest . positive but not significant effect on reading interest Keywords: Quality of Service, Infrastructure, Promotion, Interest in Reading